Issues of forming information skills of students in mathematics lessons through ICT - Elena E. Ivanova, Klara H. Karamova, Lenar M. Mukhametshin,; F. Usmanov, Salavat (Opción, 2019)
The article is devoted to the problem of forming of information skills of students in mathematics lessons using the information computer technologies in the context of the requirements of the Federal State Educational Standard via comparative qualitative research methods. As a result, the use of ICT in mathematics lessons allows students to visualize the studying material, facilitates the work of teacher, raises the level of academic results of students due to their interest. In conclusion, the use of ICT tools would inevitably become a way of improving the quality of mathematical education.